The potential of Ganoderma lucidum extracts as bioactive ingredients in topical formulations, beyond its nutritional benefits - Taofiq, Oludemi (2018)
Ganoderma lucidum was characterized in terms of nutritional value and chemical composition. Thereafter, ethanolic Soxhlet extracts were evaluated for antioxidant, anti-inflammatory, antityrosinase, antimicrobial and cytotoxic effects, and further characterized in terms of phenolic acids, polysaccharides and triterpenoids. Finally, the obtained extracts were tested as cosmeceutical ingredients. G. lucidum proved to be a source of macronutrients and important bioactive compounds such as terpenoids, specially triterpenoids, and polysaccharides. In the extracts, ganoderic acids C2, A and H were the most abundant triterpenic acids and protocatechuic, p-hydroxibenzoic and syringic acids the identified phenolics. The developed cosmeceutical formulation preserved the extract bioactivities, presented a light-yellow colour and a pH of 4.6, which is considered appropriate for cosmeceutical's design. Behind the important nutritional/bioactive composition of G. lucidum, a potential towards its valorisation in the field of cosmeceuticals is foreseeable, as deduced from the bioactivities of its ethanolic extract and preservation in the tested formulation.